Decoupling of Medical Public-Private Partnership Efficiency and Pollution to Improve Public Health: A Three-Stage DEA Analysis - Chien-Chi Chu; Zhi-Hang Zhou; Bin Sun; Zhan-Jie Wen; Yu-Yang Ma (Frontiers Media S.A., 2021)
This study investigates the spatiotemporal evolution of the efficiency of medical public-private partnerships (PPPs) and the decoupling of environmental pollution to promote public health, balanced development, and environmentalism. Based on the 2011-2020 data of medical PPPs in China, the results of a three-stage data envelopment analysis (DEA) and decoupling model show that, firstly, the spatiotemporal evolution of PPP efficiency of China in healthcare has forward periodic twists and turns, and alternating peaks and valleys, which fall into two stages: extensive development, and transformation and upgrading. Secondly, this development is either a type of stable, steady or a surge increase. Thirdly, PPP efficiency and environmental pollution show a weak decoupling state. That is, Northeast China (NEC) and Southwest China (SWC) are in a state of increasing connection, whereas Northwest China (NWC) is in an expanding negative decoupling state. The remaining regions are in a weak decoupling state. This study recommends the mode of ecology-oriented development (EOD) to promote a high-quality, integrated development of PPPs in medicine and healthcare that are especially conducive to a "green economy." There should be a more coordinated development across regions in China as well.